IMPLEMENTASI UNDANG-UNDANG NOMOR 32 TAHUN 2002 TENTANG PENYIARAN OLEH MEDIA PENYIARAN DI NTB (Studi di TV 9 Lombok) - GEDE TUSAN ARDIKA (GANEC SWARA, 2020)
The use of the internet in changing the way consumers communicate and consume television media content is known as "media disruption". This disruption or disruption occurs because of technological changes and the innovations that follow. This disruption or disruption to innovation has made a number of televisions competing to take advantage of the development of the internet in creating content, both entertainment and news content, where in this era of disruption television broadcast content is filled with content that takes content from the internet such as Youtube and other streaming social media.With the existence of broadcast program regulations that take snippets of images and / or sound clips from other broadcasting institutions, researchers are interested in knowing more about broadcast programs and the implementation of Law Number 32 Year 2002 concerning Broadcasting.This study aims to determine the implementation and obstacles of Law Number 32 Year 2002 concerning broadcasting by Lombok TV9 broadcasting media in the era of disruption.This research is a normative empirical research with a research approach using a statutory approach, a conceptual approach, a case perspective and a comparative perspective. Types and sources of research data are primary data and secondary data with primary and secondary legal materials. Data collection techniques in the form of interviews, literature study and documentation.The results of this study indicate that TV9 Lombok in implementing Law Number 32 of 2002 concerning Broadcasting in the era of disruption has not been implemented properly due to several obstacles including: lack of coordination and knowledge of broadcasting regulations and not carrying out the stages of television program programs properly.